TANGGUNG JAWAB PPAT (PEJABAT PEMBUAT AKTA TANAH) ATAS PERALIHAN HAK ATAS TANAH TANPA KEHADIRAN PEMEGANG HAK - INKA KRISTINA GULTOM (jurnal.unprimdn.ac.id, 2020)
Transfer of land title is a legal action to transfer one’s land title to another. It can only be registered if it is proven with a deed issued by Officials Empowered to Draw up Land Deeds (PPAT). The drawing up of PPAT deeds have to be attended by all parties involved in the legal action, but in the case stated in ruling number 48/G/2014/PTUN/Mdn, PPAT issues a Sale and Purchase Deed without the attendance of the land title holder. This thesis discusses about how the process of land title transfer according to the prevailing laws and regulations in Indonesia, how about the legal protection for land title holders against the land title transfer that is made by PPAT without their attendance, and how about the liabilities of PPAT for the land title transfer that is made without the attendance of the land title holder. This is a normative juridical research with descriptive analysis. The data used to answer the research problems consist of primary and secondary data sourced from library and field research. The results of this research provides conclusion, process of land title transfer pursuant to the prevailing laws and regulations that can be made through sales and purchases, exchanges, grants, income in companies and the other legal actions to transfer rights, except the transfer of rights through an auction. If PPAT issues or draws up a deed of sale and purchase on transfer of land title without the attendance of all parties or the land title holder, the deed becomes null and the land title certificate cannot be transferred if the owner does not want it; and the land title holder is rightful to file a claim to take his rights back if it is taken or transferred to another party without his permission. Due to the negligence and mistakes of PPAT in issuing a deed of transfer, PPAT shall be liable for his actions civilly, criminally and administratively in case his legal action in the transfer of land title has harmed any party or the land title holder. In this case, the PPAT has good intentions, acknowledges his mistakes and is willing to become a witness at the state administrative court to provide testimony on truth of the facts put in the deed that he has issued.